Spiderman : the amazing story - Saunders, Catherine; Marvel Comics Group (New York : DK, 2006)
The story of how Peter Parker acquired super powers and became Spiderman.
"Marvel"--Cover.
Keywords: Spider-Man (Fictitious character) -- Juvenile fiction; Heroes -- Juvenile fiction; Spider-Man (Fictitious character) -- Fiction; Heroes -- Fiction